Enabling Private Sector Engagement in Disaster Resilience in South and East Asia. Issue 4 (17th July 2019) - Mavrodieva, Aleksandrina V.; Shaw, Rajib
Abstract : Businesses are closely related with communities not only as providers of goods but also as job market creators. The timely and efficient recovery of business operations is crucial for serving the basic needs of disaster‐stricken communities and the continuation of daily life activities, thus speeding up the return to "normalcy." The majority of private business is still unaware of the possibilities, opportunities, and advantages of engaging in disaster risk reduction (DRR)‐related initiatives. The current paper argues that information sharing, access to funding, adequate and easy‐to‐understand and to follow rules and regulations, and functioning public institutions with designated coordinating bodies need to be in place to enable this process. This study concludes that coordinated, tailored, continuous efforts by both businesses and the public sector, supported by international organizations, will be needed to tackle the complex web of disaster challenges now and in the decades to follow. The paper will focus on East and South Asia as some of the most disaster‐prone regions in the world, without comparing the success rate between the individual countries. It is, instead, intended as a perspective paper, aiming to provide a broad regional overview of some of the challenges and opportunities in engaging the private sector in disaster management, and to present some high‐level policy suggestions on how to better address the existing issues. 促使东南亚私人部门参与灾害恢复力行动: 商业作为物品提供者和工作市场创造者, 与社区紧密相关。商业活动恢复的及时性和有效性, 对服务受灾社区的基本需求和对维持每日生活而言至关重要, 这样才能让一切加速回归"常态"。绝大多数私人企业仍然没有意识到, 参与降低灾害风险的倡议所带来的可能性, 机遇和优势。本文认为, 信息共享、资金的可获取性、规则和监管制度的充足性、易理解性和易执行性, 以及拥有协调机构的现有公共机构, 这些因素都需要落实才能促使私人企业参与降低灾害风险这一过程。本文结论认为, 为应对现有灾害挑战和未来几十年间灾害挑战所组成的复杂网络, 需要具备协调性和定制性的持续努力, 而这些努力则依靠企业自身、国家公共部门、区域组织和国际组织发起共同倡议。 本文将聚焦于东南亚这一在全球属于最易受灾害影响的区域国家, 但本文并未比较个别国家之间的减灾成功率。本文作为一篇观点文章, 致力就私人部门参与灾害管理时产生的一些挑战和机遇提供一个广泛的区域概括, 同时就如何更好地应对现有问题提供一些高质量政策建议。 Permitiendo la participación del sector privado en la resiliencia ante desastres en el sur y este de Asia: Las empresas están estrechamente relacionadas con las comunidades como proveedores de bienes, pero también como creadores del mercado laboral. La recuperación oportuna y eficiente de las operaciones comerciales es crucial para atender las necesidades básicas de las comunidades afectadas por el desastre y la continuación de las actividades de la vida diaria, acelerando así el retorno a la "normalidad". La mayoría de las empresas privadas aún desconocen las posibilidades, oportunidades y ventajas de participar en iniciativas relacionadas con la RRD. El documento actual sostiene que el intercambio de información, el acceso a la financiación, las reglas y regulaciones adecuadas y fáciles de entender y las instituciones públicas que funcionan con los organismos coordinadores designados deben estar en su lugar para permitir este proceso. Este estudio concluye que se necesitarán esfuerzos coordinados, personalizados y continuos, que dependen de la iniciativa combinada de las propias empresas, el sector público nacional y las organizaciones regionales e internacionales, para enfrentar la compleja red de desafíos de desastres ahora y en las próximas décadas. El documento se centrará en el este y el sur de Asia como una de las regiones más propensas a desastres en el mundo, sin comparar la tasa de éxito entre países individuales. En su lugar, está pensado como un documento de perspectiva, con el objetivo de proporcionar una visión general regional de algunos de los desafíos y oportunidades para involucrar al sector privado en la gestión de desastres, y presentar algunas sugerencias de políticas de alto nivel sobre cómo abordar mejor los problemas existentes.